Dhat dan Sifah Tuhan dalam Konsep Tauhid Muktazilah - Amal Fathullah Zarkasyi (Islamica: Jurnal Studi Keislaman, 2010)
In Islamic thought, Mu?tazilah has been classified as a rational form of current of thought. This paper is interested in exploring in a deeper manner this Mutazilite rationalism be referring specirfically to its concept of tauhid. We argue that Mu?tazilah is concerned simply with presenting this concept in its purest form. Hence, they reject the notion of God having similarity with His creatures (tashb?h) and of Him having earthly body (tajs?m). Interestingly however, the Muktzilah is not always consistent with this general hypothesis, and argue for example that the attributes of God?like His words, the Qur?an?are created (makhl?q). We will try to expose that inconsistence as part of our critique to the Mu?tazilah. The paper will also discuss proportionately the problems of tawh ?d rub?b?yah and tauhid al-dh?t wa al-s ifah, of which the Mu?tazilah has given reasonably especial attention. With regard to tauhid ul?h?yah, the paper will only speak in general terms considering that the concept has not recived a clear explanation of the Mu?tazilah. We understand nonetheless that this latter concept is about a rasional argumentation concerning the existence of God.